2019
DOI: 10.7759/cureus.4838
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Anesthesiology Educational Research for 2017

Abstract: Background Critical appraisals provide a method for establishing the status of an area of study or evaluating the effectiveness of literature within it. The purpose of this study was to review and appraise studies published in 2017 on medical education in anesthesiology and to provide summaries of the highest-quality medical education research articles in the field. Methods Three Ovid MEDLINE databases, Embase.com , Education Resources Information Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Regarding the first outcome measures (targeted research activities), the study results demonstrated significantly improved indices (i.e. defining research priorities, defining research fields of interest, and defining research teams; Table 2), which were in concordance with similar studies; these indices denote that there has been im- proved definition for "Field of interest in research" associated with "Specialized research process", resulting in "Improved quality of research", "Novelty in research areas" and "Publishing in high-impact journals" (36,71,72).…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the first outcome measures (targeted research activities), the study results demonstrated significantly improved indices (i.e. defining research priorities, defining research fields of interest, and defining research teams; Table 2), which were in concordance with similar studies; these indices denote that there has been im- proved definition for "Field of interest in research" associated with "Specialized research process", resulting in "Improved quality of research", "Novelty in research areas" and "Publishing in high-impact journals" (36,71,72).…”
Section: Discussionsupporting
confidence: 56%
“…The methods we used for this appraisal closely follow the methods for the Critical Appraisal of Anesthesiology Educational Research for 2019. 3 For the 2019 iteration, we modified the methodology to highlight articles that were especially innovative and relevant to educators, not just the articles with the most rigorous study design and implementation. Much of the description of the methodology for this study is added here verbatim from that article with some additional modifications.…”
Section: Article Identificationmentioning
confidence: 99%
“…We followed the same inclusion and exclusion criteria used by Heitz et al in the critical appraisal of research in education in emergency medicine and in previous years' critical appraisals of research in anesthesiology education. [2][3][4][5] We included all levels of learners (students, residents/ fellows, and practicing clinicians) and articles applicable to physicians, nurses, and other providers in the field of anesthesiology. Studies were defined as hypothesis-testing investigations, evaluations of education interventions, or explorations of educational problems.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations